PLANT SPECIES DESCRIBED BY WILLIAM GRIFFITH IN ‘SOME ACCOUNT OF THE BOTANICAL COLLECTION BROUGHT FROM THE EASTWARD BY DR. CANTOR’ - Turner, I. M. (Edinburgh Journal of Botany, 2015)
William Griffith wrote an account of the plants collected by Theodore Cantor in 1840 while on a military expedition to Chusan in China. This was published posthumously in 1854, but was also distributed in 1844 or 1845 as a preprint. The 14 new names at species rank appearing in the paper are reviewed (including the often overlooked Leucopogon ophirensis and Corylopsis grata) and their typification considered. Lectotypes are designated for 10 of these names, one second-stage lectotypification is proposed, and Corylopsis griffithii Hemsl. is also lectotypified.
Keywords: Bouea; Theodore Cantor; Corylopsis; Cucurbitaceae; Tristaniopsis; typification